Suitability of different pollen grains and Tetranychus urticae as food for the predatory mite, Amblyseius swirskii (Acari: Phytoseiidae) - Fatemeh Kadkhodazadeh; Mahdieh Asadi; Mostafa Khanamani (Persian Journal of Acarology)
The suitability of eight pollen diets (wild almond, date palm, oak, pomegranate, pistachio, peach, damask rose, and walnut) and also Tetranychus urticae Koch as natural diet on life table of the Amblyseius swirskii (Phytoseiidae) was determined at 25 ± 1 °C, 60 ± 5% relative humidity and photoperiod of 16:8 h (L: D). Results showed that damask rose pollen was not accepted as food and did not support the development of A. swirskii beyond the protonymphal and deutonymphal stage. The highest and lowest values of the intrinsic rate of increase (r) and finite rate of increase (λ) belonged to the pistachio (0.192 and 1.212 day−1) and peach (0.022 and 1.023 day−1) pollen, respectively. The net reproductive rate (R0) values varied from 1.4 offspring for the peach pollen to 29.54 offspring for the pistachio. Furthermore, the highest and lowest fecundity rate was recorded on the pistachio (36.65 eggs/female) and peach (3.23 eggs/female) pollen, respectively. Measured life table parameters of A. swirskii reared on different diets revealed pistachio, and after that, date palm and pomegranate pollen grains to be the most suitable diets. These findings may introduce more suitable pollen diets for the rearing of this predatory mite.